Pendampingan Strategi Penyusunan Modul Ajar Pada Kurikulum Merdeka Bagi Guru SD Gugus X Parepare - Mas'ud B.; Malik, Marwati Abd.; Hasanuddin, Andi ilham Akbar; Sya'ih, Fhilda Yulinda; Ningsih, Dwi; Fatirah H.B, Akhnes Intan Sari; Hasdianti; Innawati; Jumarni; Jumiana; Mirnawati (Jurnal Pengabdian Magister Pendidikan IPA, 2024)
Abstract: This research aims to evaluate the strategy for preparing teaching modules in the Independent Curriculum for elementary school teachers in Gugus X Parepare. The background to this research focuses on the importance of teaching modules as the main instrument in effective and efficient learning, which can support teachers in implementing the Independent Curriculum better. Quality teaching modules not only function as a guide for teachers, but also play a role in developing 21st century skills in students, such as critical thinking and creativity. This research method uses a community service approach which includes four stages: observation and planning, implementation, mentoring, as well as evaluation and follow-up. At the observation stage, needs were identified and objectives formulated through in-depth interviews with teachers. The implementation phase involved direct training attended by 84 elementary school teachers in Gugus X Parepare, with a focus on preparing teaching modules and implementation strategies for the Independent Curriculum. At the mentoring stage, teachers are guided in preparing teaching modules that are relevant to student needs and the local context. The evaluation stage includes collecting input, analyzing results, and planning follow-up actions to improve the teaching module. The research results show that this activity was successful in increasing teachers' understanding and skills in designing teaching modules that are in accordance with the Independent Curriculum. In this way, it is hoped that the quality of learning at Gugus X Parepare can improve significantly. Keywords: Independent Curriculum, Teaching Modules, Training, Basic Education